Role of laccases and peroxidases in saprotrophic activities in the lichen Usnea undulata. (April 2015) - Beckett, Richard P.; Ntombela, Nomcebo; Scott, Erin; Gurjanov, Oleg P.; Minibayeva, Farida V.; Liers, Christiane
Abstract: Lichens produce various oxidoreductases including heme-containing peroxidases and the copper-containing phenol oxidases tyrosinase and laccase. Our earlier findings suggested that significant oxidoreductase activity occurs mainly in lichens from the order Peltigerales. Here we show that the non-Peltigeralean lichen Usnea can display significant activities of peroxidases and laccases. Strong evidence for the involvement of peroxidases and laccases in saprotrophic activities comes from the observation that their activities are induced by "starvation" due to prolonged dark storage, and also by treatment with soluble cellulose and lignin breakdown products. We also show that, given a quinone and chelated Fe, Usnea can produce hydroxyl radicals; these radicals contribute to the break down of carbohydrates or lignin. However, hydroxyl radical production is independent of laccase and peroxidase activity. Laccases and peroxidases are involved in other aspects of lichen biology; here we show that peroxidases, but not laccases, can break down lichen substances. Reduction in the amounts of lichen substances will reduce photoprotection, which will increase the photosynthetic capacity of thalli during winter when light intensities are low.